Mobile Payment in Overspending Behavior with Gender as a Moderating Variable: Empirical Evidence from Gen Z - Hasbi (Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The exploration of the impact of mobile payment integration on consumer behavior represents a compelling avenue of inquiry within scholarly discourse. Despite the burgeoning adoption rates of mobile payment systems, empirical research delineating its ramifications on consumer spending tendencies, particularly in terms of propensity towards overspending, remains relatively sparse. Mobile payment platforms offer unparalleled convenience, facilitating transactions across diverse contexts, yet potentially precipitating a surge in consumer expenditure. This study endeavors to elucidate the intricate relationship between mobile payment usage and tendencies towards overspending, with a particular focus on Generation Z, a cohort known for its digital fluency and proclivity towards embracing technological innovations. Employing a quantitative research methodology, structural equation modeling (SEM) is employed to dissect the nuanced impact of mobile payment adoption on consumer behavior. Drawing upon a sample of 105 Generation Z respondents, data collection was conducted online via Google Forms disseminated through various social media platforms to ensure a diverse and representative sample. Furthermore, this inquiry investigates the moderating role of gender in shaping the nexus between mobile payment utilization and overspending behavior, seeking to discern potential gender-based disparities in consumer spending patterns engendered by mobile payment adoption. The findings underscore a significant positive association between mobile payment usage and proclivities towards overspending, indicating that heightened engagement with mobile payment platforms correlates with increased consumer expenditure tendencies. Moreover, gender emerges as a salient moderator in this relationship, with females exhibiting a heightened susceptibility to consumer behavior relative to their male counterparts.